Development and application of a decision support tool for biomass co-firing in existing coal-fired power plants. (1st November 2019) - Smith, Jason S.; Safferman, Steven I.; Saffron, Christopher M.
Abstract: Biomass co-firing has the potential to be a low-cost source of renewable energy that can utilize the existing infrastructure of coal-fired power plants, while reducing the overall environmental impact. Though there are technical barriers to the development of co-firing operations, including the lower calorific value and higher chlorine content of the biomass compared to coal, several systems have shown the ability to do so successfully. Applying the lessons learned from such systems to site-specific conditions in a systematic way could greatly benefit the industry. This study uses aggregated information regarding various combustion technologies, pre-treatment technologies, and available biomass feedstocks to generate a decision support tool for energy providers that will help identify economic, environmental, and social impacts of developing site-specific biomass co-firing projects at existing coal-fired power plants. The tool was verified using an existing case study and demonstrated for an existing power plant, which also served to provide general observations for similar situations. For the area studied, co-firing using 5% biomass substitution over a 20 year project life was found to be an economical option for renewable energy generation and reduced emissions. The expense of raw biomass had the largest impact on the life-cycle project cost. Torrefied pellets had the highest plant-gate cost, as compared to dried and pelleted biomass. However, the biomass pretreatment method was highly sensitive to the substitution amount and project life. Highlights: Decision support model to examine co-feeding biomass into a coal energy plant. Multiple pretreatment options and process configurations are modeled. Model calibrated and verified using case study data. Biomass co-firing is a highly competitive option for renewable energy generation. A 5% substitution of biomass was found to be economical and reduce emissions.